2019
DOI: 10.1002/hed.26001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of active smoking on outcomes in HPV+ oropharyngeal cancer

Abstract: Background: The role of smoking among patients with human papillomavirus (HPV)-positive oropharyngeal squamous cell carcinoma (OPSCC) is unclear.Methods: A retrospective cohort study of patients with HPV(+) OPSCC from 2001 to 2015 at a tertiary-care institution was conducted. The primary outcome was overall survival (OS). Results: Among 484 included patients, 94 (19.4%) were active smokers, 226 (46.7%) were former smokers, and 164 (33.9%) never smoked. Among active smokers, 82 patients (87.2%) had a ≥10 pack-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Notably, previous work has demonstrated that active smoking at diagnosis is an adverse prognostic factor in this population 13,14 . The current study extends our previous work by Xiao et al 14 and complements the work by Vawda et al 13 by analyzing time from smoking cessation as a continuous variable, using nonlinear regression, and applying the RPA methodology.…”
Section: Discussionsupporting
confidence: 71%
“…Notably, previous work has demonstrated that active smoking at diagnosis is an adverse prognostic factor in this population 13,14 . The current study extends our previous work by Xiao et al 14 and complements the work by Vawda et al 13 by analyzing time from smoking cessation as a continuous variable, using nonlinear regression, and applying the RPA methodology.…”
Section: Discussionsupporting
confidence: 71%
“…However, currently, it is crucial to fully understand how the presence of HPV interacts with other risk factors such as smoking and alcohol in HNSCC in this region [14,15]. From the etiological point of view and in terms of tumour progression and prognosis, the role of these known risk factors is still debated, and those are considered as either "HPV competitors" or as positively interacting with HPV [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with recent cohort studies that evaluated the prognostic value of smoking status at diagnosis in HPV‐associated OPC. Xiao et al reported data from 484 patients with HPV‐associated OPC treated with surgery (13% of cohort) or CRT (any systemic therapy) and found smokers at diagnosis was associated with inferior OS compared to former/never smokers (aHR 2.28 for risk of death, 95% 1.47–3.55) when adjusted for eighth edition AJCC staging 25 . Mirghani et al and Platek et al also reported smoking status at diagnosis as a significant prognostic factor for OS in HPV‐associated OPC treated with RT +/− systemic therapy (Cisplatin or Cetuximab) 15,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses of the impact of smoking on survival outcomes in HPV‐associated OPC have been performed using older staging systems that do not differentiate between HPV and non‐HPV‐associated OPC, or do not assess the impact of the systemic therapy agent used 15,23,25,26 . Two early de‐escalation trials in HPV‐associated OPC have recently shown inferior survival substituting Cetuximab for Cisplatin in patients treated with CRT 27,28 .…”
Section: Introductionmentioning
confidence: 99%